Inhibition of the PI3K/AKT/mTOR signaling promotes an M1 macrophage switch by repressing the ATF3-CXCL8 axis in Ewing sarcoma. (28th February 2023) - Palombo, Ramona; Passacantilli, Ilaria; Terracciano, Francesca; Capone, Alessia; Matteocci, Alessandro; Tournier, Simon; Alberdi, Antonio; Chiurchiù, Valerio; Volpe, Elisabetta; Paronetto, Maria Paola
Abstract: Ewing sarcomas are aggressive pediatric tumors of bone and soft tissues driven by in frame chromosomal translocations that yield fusion proteins guiding the oncogenic program. Promising alternative strategies to ameliorate current treatments involve inhibition of the PI3K/AKT/mTOR pathway. In this study, we identified the activating transcription factor 3 (ATF3) as an important mediator of the PI3K/AKT/mTOR pathway in Ewing sarcoma cells. ATF3 exerted its pro-tumoral activity through modulation of several chemokine-encoding genes, including CXCL8 . The product of CXCL8, IL-8, acts as a pro-inflammatory chemokine critical for cancer progression and metastasis. We found that ATF3/IL-8 axis impacts macrophages populating the surrounding tumor microenvironment by promoting the M2 phenotype. Our study reveals valuable information on the PI3K/AKT/mTOR derived chemokine signaling in Ewing sarcoma cells: by promoting ATF3 and CXCL8 downregulation, inhibition of the PI3K/AKT/mTOR signaling promotes a proinflammatory response leading to upregulation of the protective anti-tumoral M1 macrophages. Highlights: Inhibition of the PI3K/mTOR signaling impacts tumor microenvironment via ATF3 in Ewing sarcoma (ES). Activation of the ATF3 - IL8 axis promotes M2 macrophage polarization in ES. IL-8 upregulation correlates with worse prognosis of ES patients. Inhibition of ATF3-IL-8 cascade favors M1 macrophage phenotype hampering tumor invasion.